2020
DOI: 10.1002/cbin.11468
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic gene TRIM10 confers resistance to cisplatin in osteosarcoma cells and activates the NF‐κB signaling pathway

Abstract: Deregulation of tripartite motif (TRIM) family proteins contribute to multiple biological processes such as neurodegeneration, development, inflammation, cell survival, apoptosis, and carcinogenesis. However, the biological function and molecular mechanism of TRIM family proteins in osteosarcoma chemoresistance remain unclear. In the current study, we found the protein expression of TRIM10 was markedly overexpressed in cisplatin resistance's osteosarcoma tissues and TRIM10 overexpression was inversely correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The regulation of the TRIMs for the NF-κB signaling pathway is diverse, and some members of the triple structural domain protein family are involved in the activation of the NF-κB signaling pathway, for example, TRIM1 is involved in the tumor necrosis factor (TNF) α/LPS-induced activation of the NF-κB signaling pathway (26), TRIM52 acts as a positive regulator to regulate the NF-κB signaling pathway (27), and TRIM22 also has an activating effect on the NF-κB signaling pathway (28). It has been reported that TRIM22/ activates NF-κB signaling in glioblastoma by accelerating the degradation of IκBα (29); TRIM47 activates NF-κB signaling via PKC-ε/PKD3 stabilization and contributes to endocrine therapy resistance in breast cancer (30), and TRIM10 activates the NF-κB signaling pathway in osteosarcoma (31). In contrast, some members of the triple structural domain protein family down-regulate the NF-κB signaling pathway in some tumors, namely, TRIM39 inhibits the NF-κB signaling pathway by stabilizing actin expression (32), and TRIM45 inhibits tumor cell proliferation by suppressing the NF-κB signaling pathway (33).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the TRIMs for the NF-κB signaling pathway is diverse, and some members of the triple structural domain protein family are involved in the activation of the NF-κB signaling pathway, for example, TRIM1 is involved in the tumor necrosis factor (TNF) α/LPS-induced activation of the NF-κB signaling pathway (26), TRIM52 acts as a positive regulator to regulate the NF-κB signaling pathway (27), and TRIM22 also has an activating effect on the NF-κB signaling pathway (28). It has been reported that TRIM22/ activates NF-κB signaling in glioblastoma by accelerating the degradation of IκBα (29); TRIM47 activates NF-κB signaling via PKC-ε/PKD3 stabilization and contributes to endocrine therapy resistance in breast cancer (30), and TRIM10 activates the NF-κB signaling pathway in osteosarcoma (31). In contrast, some members of the triple structural domain protein family down-regulate the NF-κB signaling pathway in some tumors, namely, TRIM39 inhibits the NF-κB signaling pathway by stabilizing actin expression (32), and TRIM45 inhibits tumor cell proliferation by suppressing the NF-κB signaling pathway (33).…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of the IFN‐I signaling pathway has multiple implications in the treatment of endotoxic shock caused by Gram‐negative pathogens, as well as in autoimmune conditions such as rheumatoid arthritis and SLE. A recent study reported that TRIM10 is highly expressed in chemotherapy‐resistant osteosarcoma tissues and promotes cisplatin resistance in osteosarcoma cells, demonstrating that it may be involved in the development of osteosarcoma [41]. Indeed, TRIM family members, such as TRIM26 and TRIM36, have various functions in modulating cancer development and progression [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…206 The oncogene TRIM10 upregulates nuclear levels of p65, thereby activating classical NF-κB signaling to promote cisplatin resistance in OS cells. 207 Contemporary research on NF-κB-associated mechanisms in OS is centered on the modulation of miRNAs and lncRNAs that are possible upstream modulators of NF-κB and could exert their oncogenic or their inhibitory properties on tumors by affecting the levels of STAT3 expressed in OS cells. 208,209 When the expression of lncRNA NKILA was detected in 60 cases of OS and adjacent tissues, lncRNA NKILA expression was found to be reduced in OS tissues, and the proliferation, invasive rate, and migration of OS cells were enhanced after transfection of NKILA-siRNA with cells, while the NF-κB inhibitor (JSH) could reverse the inhibitory impact of NKILA on cell migration and proliferation, implying that lncRNA NKILA is involved in OS development and acts through the NF-κB/NAIL signaling pathway.…”
Section: Nf-κb Signaling Pathway and Os Development And Progressionmentioning
confidence: 99%
“…Notably, alpha thalassemia and intellectual disability syndrome X‐linked (ATRX) deficiency promotes OS cell invasion by increasing NF‐κB signaling and integrin β3 binding 206 . The oncogene TRIM10 upregulates nuclear levels of p65, thereby activating classical NF‐κB signaling to promote cisplatin resistance in OS cells 207 …”
Section: Signaling Pathways In Osmentioning
confidence: 99%